Inflammation interferes with chemoreception in pigs by altering the neuronal layout of the vomeronasal sensory epithelium - Mechin, Violaine; Asproni, Pietro; Bienboire-Frosini, Cécile; Cozzi, Alessandro; Chabaud, Camille; Arroub, Sana; Mainau, Eva; Nagnan-Le Meillour, Patricia; Pageat, Patrick (Frontiers in Veterinary Science, 2022)
Chemical communication is widely used by animals to exchange information in their environment, through the emission and detection of semiochemicals to maintain the social organization and hierarchical rules in groups. The vomeronasal organ (VNO) is one of the main detectors of these messages, and its inflammation has been linked to behavioral changes since it potentially prevents molecules detection and thus the translation of the signal into action. Our previous work highlighted the link between the intensity of the vomeronasal sensorial epithelium inflammation and intraspecific aggression in pigs. The aim of this study was to evaluate the cellular and molecular changes occurring during vomeronasalitis in 76 vomeronasal sensorial epitheliums from 38 intensive-farmed pigs. Histology was used to evaluate the condition of each VNO and to classify them into healthy, weak, moderate, or strong inflammation. This data was compared to the thickness of the sensorial epithelium and to the number of type 1 vomeronasal receptor cells, using anti-Gαi2 protein immunohistochemistry and ImageJ software analysis. The presence of odorant-binding protein in glands surrounding the VNO was also analyzed by immunohistochemistry and compared to inflammation intensity since its role as molecules transporter to sensory neurons has been well established. Of the 76 samples, 13 (17%) were healthy, 31 (41%) presented a weak inflammation, and 32 (42%) a moderate inflammation. No strong inflammation was observed. The epithelium thickness and the number of Gαi2+ cells were inversely correlated to the inflammation intensity (Kruskal-Wallis and ANOVA tests, p<0.0001), while the odorant-binding protein expression in vomeronasal glands was increased in inflamed VNO (Kruskal-Wallis test, p=0.0094), regardless of the intensity. This study brings new elements concerning the characterization of the VNO inflammation and the mechanisms with which it interferes with chemoreception and animal behavior. Inflammation was associated with a reduction of the sensory epithelium thickness and the Gαi2+ cells number, suggesting that this condition can induce different degrees of neuronal loss. This finding could explain how vomeronasalitis may prevent the correct functioning of chemical communication leading to social conflicts with a potential negative impact on welfare, which is one of the most important challenges in pig farming.